HUBUNGAN ANTARA JENIS KELAMIN DENGAN KEJADIAN TEMPERTANTRUM PADA ANAK USIA 3-5 TAHUN DI TK WILAYAH TUMPANG KABUPATEN MALANG - eka supriyanti; Agnis Sabat Kristiana; Evi Dwi Prastiwi; Tanti Budhi Hariyanti (Journal of Nursing Care and Biomolecular, 2022)
Introduction: In Indonesia, toddlers who experience tantrums within one year are 23%-83% of children aged 2-4 years. According to Wakschalg, 1,500 parents who have children, the majority of whom are toddlers (83.7%) experience tantrums, 8.6% of whom are angry and tantrums every day. Many factors cause children to experience tempertantrums, one of which is the family environment in which there is gender, children who have a male gender are more emotional than children who have a female gender. The purpose of this study was to determine the relationship between gender and the incidence of tempertantrums in children aged 3-5 years. The design used correlation analytic with cross sectional approach. Method: The population is parents who have children aged 3-5 years, the sample is parents who have children with temper tantrums according to the inclusion criteria with purposive sampling technique. The research location is in the Tumpang Region Kindergarten, Malang Regency. Collecting data using a questionnaire. Data analysis using Chi Square Test. Result and Analysis: The results showed P = 0.002 (P <0.05) meaning that there was a significant relationship between the sex of the child and the incidence of tempertantrums.   Keywords: Gender; Tempertantrums; Child.